Effect of the ZiBuPiYin Recipe on Diabetes-Associated Cognitive Decline in Zucker Diabetic Fatty Rats After Chronic Psychological Stress - Bi, Tingting; Zhan, Libin; Zhou, Wen; Sui, Hua (Frontiers in Psychiatry, 2020)
Background Cognitive impairment is a complication of type 2 diabetes mellitus (T2DM) that affects the central nervous system (CNS). Studies have shown that chronic psychological stress may promote the development of T2DM into diabetes-associated cognitive decline (DACD). Previously, cognitive impairment in T2DM was correlated predominantly with insulin resistance in the medial prefrontal cortex (mPFC). Aims We examined the effect of the ZiBuPiYin recipe (ZBPYR) on Zucker diabetic fatty (ZDF) rats and explored the impact of chronic stress on altered β-amyloid (Aβ) metabolism through insulin receptor substrate (IRS) 1/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway after the induction of chronic psychological stress. Main Methods After chronic psychological stress and drug treatment, cognitive function was observed via behavioral experiments. The activation of the hypothalamus-pituitary-adrenal (HPA) axis and levels of Aβ were detected by enzyme-linked immunosorbent assay, and the expression of related proteins was evaluated by Western blotting. Key Findings ZBPYR treatment significantly decreased anxious-like behaviors and plasma corticosterone (CORT) levels, and ameliorated learning and memory impairments of ZDF rats after chronic psychological stress. ZBPYR also reduced the deposition of Aβ in the mPFC, improved brain insulin resistance, and modulated the mTOR-autophagy pathway. Significance ZBPYR may be a potential therapeutic application for the treatment of DACD induced by chronic psychological stress.